The potential role of cfDNA-related innate immune responses in postoperative bone loss after alveolar bone grafting - Huang, Hanyao; Yang, Renjie; Shi, Bing (Frontiers in Immunology, 2023)
The purpose of treating alveolar bone cleft is to restore a normal maxilla structure. Multiple factors have been identified that can affect the success of alveolar bone grafting. However, with consistent treatment modifications, the surgical outcomes have been improved, but alveolar bone loss still exists. Thus, a new aspect should be found to solve this problem. As alveolar bone belongs to the periodontal tissues, the mechanism of the alveolar bone loss after bone grafting in patients with alveolar bone cleft may be similar to the development of alveolar bone loss in periodontitis. Cell-free DNA (cfDNA) has been demonstrated as a key promoter of alveolar bone loss during periodontal inflammation. We hypothesized that cfDNA-related innate immune responses could be a major inducement for postoperative bone loss after alveolar bone grafting. In this perspective, we preliminarily proved the potential association between cfDNA, TLR9 pathway, and alveolar bone grafting operation, and it might verify that surgical trauma could accumulate cfDNA, which can further activate cellular TLR9 signaling.